(untitled) (Journal of the College of Education for Women, 2019)
The problem of the current paper is embodied in the weakness of the female studentsof the department of the Quran sciences in the college of Education for Women in theUniversity of Baghdad in the subject of reciting and memorizing the Holy Quran. This is whatthe professors and the scientific and educational supervisors stress equally through their visitsto the students applicants during the period of their practical application of teaching in theschools; especially that the subject is thought for four years during their study in the college.That weakness is so explicit with a quite large number of the students-applicants, who aresupposed to be the future teachers in the subject of the Holy Quran and Islamic Education inthe intermediate and secondary schools. Hence come the importance of finding the solutionsfor such a big problem as its main issue is totally related to the greatest divine Book of all, theHoly Quran, on one hand; and on the other hand, it is related to the out puts of the departmentof the Quran sciences and Islamic Education that is related to preparing qualified graduates toteach the Holy Quran in our schools.Therefore, the researchers have chosen to investigate the problem of teaching thesubject of the Holy Quran recitation and its memorization through the perspectives of theteachers and the students and try to find the best solutions for them